2008
DOI: 10.1093/aje/kwn122
|View full text |Cite
|
Sign up to set email alerts
|

Body Size and Renal Cell Cancer Incidence in a Large US Cohort Study

Abstract: Renal cell cancer (RCC) incidence has increased in the United States over the past three decades. The authors analyzed the association between body mass index (BMI) and invasive RCC in the National Institutes of Health (NIH)-AARP Diet and Health Study, a large, prospective cohort aged 50-71 years at baseline initiated in 1995-1996, with follow-up through December 2003. Detailed analyses were conducted in a subcohort responding to a second questionnaire, including BMI at younger ages (18, 35, and 50 years); wei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
108
0
7

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 162 publications
(125 citation statements)
references
References 41 publications
10
108
0
7
Order By: Relevance
“…Some studies used figure drawings depicting progressively larger body shapes as proxy measures of body size at certain age periods [26][27][28][29][30]. In some cases, studies assessed only weight at the late adolescent period, relying mainly on participants' retrospective recall of their weight during a period of adolescence, and current height was either self-reported or measured to calculate BMI [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Measured height and weight from childhood or adolescence were available in a small subset of studies [51][52][53][54][55][56][57][58][59][60][61].…”
Section: Weight and Cancermentioning
confidence: 99%
“…Some studies used figure drawings depicting progressively larger body shapes as proxy measures of body size at certain age periods [26][27][28][29][30]. In some cases, studies assessed only weight at the late adolescent period, relying mainly on participants' retrospective recall of their weight during a period of adolescence, and current height was either self-reported or measured to calculate BMI [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. Measured height and weight from childhood or adolescence were available in a small subset of studies [51][52][53][54][55][56][57][58][59][60][61].…”
Section: Weight and Cancermentioning
confidence: 99%
“…1,2 With the obesity rate on the rise, it is likely that RCC will be diagnosed in more obese patients. A standard treatment modality for small renal masses is nephronsparing surgery.…”
Section: Introductionmentioning
confidence: 99%
“…59,60,62,65,70,71,78,[83][84][85] Most studies have found an association with elevated body mass index (BMI) among both men and women, and abdominal obesity, as indicated by waist-to-hip ratio, 58,65,70,71,85 may play an important role in this association, particularly among women. A quantitative review of the published literature reported a summary relative risk for renal cell cancer of 1.07 per unit increase of BMI.…”
Section: Obesitymentioning
confidence: 99%